Dual magnetic field and temperature optical probes of controlled crystalline phases in lanthanide-doped multi-shell nanoparticles. Issue 35 (3rd September 2021) - Ferreira, Flavia de Sousa; de Morais, Amanda Justino; Santos Calado, Claudia Manuela; Iikawa, Fernando; Couto Junior, Odilon D. D.; Brunet, Gabriel; Murugesu, Muralee; Mazali, Italo O.; Sigoli, Fernando A.
Abstract : Dual magnetic and temperature optical probes of hierarchically structured core@multi-shell nanoparticles with controlled crystalline phases: a magneto cubic core containing Dy III and a co-doped Er III :Yb III : Nd III optical hexagonal shell. Abstract : The engineering of core@multi-shell nanoparticles containing heterogeneous crystalline phases in different layers constitutes an important strategy for obtaining optical probes. The possibility of obtaining an opto-magnetic core@multi-shell nanoparticle capable of emitting in the visible and near-infrared ranges by upconversion and downshifting processes is highly desirable, especially when its optical responses are dependent on temperature and magnetic field variations. This work proposes the synthesis of hierarchically structured core@multi-shell nanoparticles of heterogeneous crystalline phases: a cubic core containing Dy III ions responsible for magnetic properties and optically active hexagonal shells, where Er III, Yb III, and Nd III ions were distributed. This system shows at least three excitation energies located at different biological windows, and its emission intensities are sensitive to temperature and external magnetic field variations. The selected crystalline phases of the core@multi-shell nanoparticles obtained in this work is fundamental to the development of multifunctional materials with potential applications as temperature and magnetic field optical probes.